2011
DOI: 10.1007/s13197-011-0548-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of bread produced from wheat, rice and maize flours

Abstract: Rice (Oryza sativa) flour and maize (Zea mays) meal substitution in wheat (Triticum aestivum) flour, from 0 to 100% each, for the production of bread was investigated. The proximate analysis, pasting properties, bread making qualities of raw materials and sensory evaluation of the bread samples were determined. The pasting temperature increased with increased percentage of rice flour and maize meal. But the other pasting characters decreased with the higher proportion of rice flour. The baking absorption was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 6 publications
0
34
0
1
Order By: Relevance
“…Generally, viscosity patterns of maize traits lacked of a clear peak viscosity, showing a continuous increase in viscosity during heating and cooling, although two deep slopes were detected initially after the onset temperature and then at the end of the cooling gradient. Rai et al (2012) found that substitution of wheat flour by rice or maize altered the pasting properties and breadmaking qualities. The lowest maximum viscosity at 95°C was obtained for Tremesino, which together with Tuy showed the lowest final viscosity; both populations had also the lowest flotation index and thus have the grains with the highest density.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, viscosity patterns of maize traits lacked of a clear peak viscosity, showing a continuous increase in viscosity during heating and cooling, although two deep slopes were detected initially after the onset temperature and then at the end of the cooling gradient. Rai et al (2012) found that substitution of wheat flour by rice or maize altered the pasting properties and breadmaking qualities. The lowest maximum viscosity at 95°C was obtained for Tremesino, which together with Tuy showed the lowest final viscosity; both populations had also the lowest flotation index and thus have the grains with the highest density.…”
Section: Resultsmentioning
confidence: 99%
“…However there was no significant difference (p≥0.05) between control and 10% LMF incorporated bread for loaf weight, volume and specific volume (Fig 1 and 2). Rai et al (2011) and Ballolli et al (2014) also reported a decrease in loaf size with a progressive increase in the proportion of non gluten flour such as maize meal and rice flour and foxtail millet flour respectively. However, loaf weight is basically determined by the quantity of dough baked and the amount of moisture and carbon dioxide diffused out of the loaf during baking (Shittu et al 2007).…”
Section: Physical Characteristics Of Breadsmentioning
confidence: 94%
“…Veluppillai et al (2010) reported that WF substitution with 35% malted rice flour was the best according to the physical and sensory quality of the bread. Rai et al (2011) reported that 25% replacement of WF by rice flour was found to be more acceptable than the control wheat bread. Hence millet flour substitution up to 30% in WF for baking bread can be considered for acceptable sensory attributes with little to no significant differences from wheat bread.…”
Section: Sensory Analysismentioning
confidence: 99%
“…As can be seen in Table 4, a reduction tendency was found as a result of increase in the amount of BR flour application and the flat bread made from blend flour with 5 % BR flour fortification was highly satisfactory and the highest overall quality score was given to the samples containing 5 % BR flour (4.2 ±0.92) and was found as a threshold for acceptable amount of BR flour being incorporated. However, Rai et al (2011) indicated that the bread samples made from wheat 25 %: rice 75 % blend flour was given the best acceptability scores by panelists and Kaur et al (2011) showed that samples incorporated with 50 % rice bran oil was slightly scored higher than others.…”
Section: Extensographic Properties Of the Doughmentioning
confidence: 98%